USB mug warmer - Aminurrasyid, Abas (2008)
The using of USB technology is quite popular in this era. We can prove it by looking at the latest products which using it such as USB fan, USB lamp, USB mouse, USB printer and many other types of equipment. Another proves is by looking at the specification of latest computer. For example, latest laptop does not provide other port except USB port. Usually, we can found another port such as parallel port and serial port at Personal computer (PC) only. For this PSM project, UBS will be using as power supply for this mug warmer.